2008
DOI: 10.3858/emm.2008.40.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Multi-transmembrane protein K15 of Kaposi's sarcoma-associated herpesvirus targets Lyn kinase in the membrane raft and induces NFAT/AP1 activities

Abstract: Viral proteins of γ-2 herpesviruses, such as LMP2A of Epstein Barr virus (EBV) and Tip of herpesvirus saimiri (HVS) dysregulate lymphocyte signaling by interacting with Src family kinases. K15 open reading frame of Kaposi's sarcoma associated herpesvirus (KSHV), located at the right end of the viral genome, encodes several splicing variants differing in numbers of transmembrane domains. Previously, we demonstrated that the cytoplasmic tail of the K15 protein interfered with B cell receptor signal transduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that the KSHV K15 transmembrane protein has the ability to interact through its cytoplasmic domain with a range of cellular proteins and thereby triggers signaling cascades (2,3,6,7,10,21,35,38). Several sequence motifs, such as the putative SH2 and SH3 binding motifs, are located in the C-terminal domain, and an involvement in K15-mediated signaling has been shown for some of these.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the KSHV K15 transmembrane protein has the ability to interact through its cytoplasmic domain with a range of cellular proteins and thereby triggers signaling cascades (2,3,6,7,10,21,35,38). Several sequence motifs, such as the putative SH2 and SH3 binding motifs, are located in the C-terminal domain, and an involvement in K15-mediated signaling has been shown for some of these.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite likely that other KSHV-encoded proteins are also palmitoylated, and this palmitoylation may be integral to their function. For example, K15, a homologue of LMP2A, is thought to target the major B cell Src kinase Lyn to lipid rafts (3,28). There are many cysteine residues present in K15, and at least one is predicted to be cytosolic.…”
Section: Discussionmentioning
confidence: 99%
“…Several critical tyrosine residues within these motifs are constitutively phosphorylated by cellular Src family tyrosine kinases, which mediate activation of downstream signaling pathways. Pathways activated by K15 signaling include the Ras/MAPK, JNK/SAPK, and NFκB pathways as well as the NFAT/AP1 transcription factors (Brinkmann et al, 2003; Brinkmann et al, 2007; Cho, Choi, & Choi, 2008). This signaling activates transcription of a number of cellular cytokines and chemokines including IL6, IL8, CCL20, CCL2, CXCL3, IL-1α/β, and Cox2 (Brinkmann et al, 2007; Wang et al, 2007).…”
Section: Lytic Kshv Proteins Involved In Cell Growth and Survivalmentioning
confidence: 99%
“…K15 can also downregulate signal transduction and intracellular calcium mobilization induced by the BCR, which may help the virus maintain latency (Choi et al, 2000). A potential mechanism by which K15 accomplishes this may be through K15’s interaction with the tyrosine kinase Lyn, which plays a role in the regulation of BCR signaling (Cho et al, 2008). Additionally, the K15 M allele induces cell motility, and this is dependent on K15-mediated upregulation of the human miRNAs miR-21 and -31 (Tsai et al, 2009).…”
Section: Lytic Kshv Proteins Involved In Cell Growth and Survivalmentioning
confidence: 99%